Strategi E-Marketing dengan Pemanfaatan Influencer terhadap Keputusan Pembelian : Studi Kasus Brand Miniletics - Laisya Kezia Clarinta; Rusdi Hidayat (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In the digital era, online marketing plays a key role in achieving company targets. This research discusses online marketing strategies through E-Marketing with a campaign management approach supported by the presence of influencers. Using influencers, as experts in various fields, strengthens marketing messages by increasing credibility and appeal. This research focuses on evaluating the Mega Sale 11.11 campaign implemented by the Miniletics brand, with a special focus on the use of influencer marketing. The results of this research show that the targets set in the Mega Sale 11.11 campaign by utilizing influencer marketing still require improvement. Therefore, the aim of this research is to evaluate E-Marketing strategies by utilizing influencers on consumer purchasing decisions.